2017
DOI: 10.3109/13668250.2017.1350834
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual care for people with intellectual and developmental disability: An exploratory study

Abstract: Sango, P.N. and Forrester-Jones, Rachel (2017) Spiritual care for people with intellectual and developmental disability: an exploratory study.Background: A faith-based (pseudonym, Adam's House-AH) and a non-faith based care service (pseudonym, Greenleaves-GL) were explored to find out if and how spiritual support was provided for people with intellectual and developmental disabilities (IDD). Method:Six months were spent volunteering within each service and a mixed-methods approach was utilised including appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Yet research (e.g. Turner et al, 2004;Sango and Forrester-Jones, 2017); practice (see Carter, Biggs, and Boehm, 2016;Sango and Forrester-Jones, 2019;Bartelli et al, 2020) and policy (Sango and Forrester-Jones, 2014;Whiting and Gurbai, 2015) indicate that little attention has been paid to this aspect of people's lives; whilst the spiritual rights of children are recognised in the United Nations Convention on the Rights of the Child (UNCRC) they do not feature in the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) (see Whiting and Gurbai, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet research (e.g. Turner et al, 2004;Sango and Forrester-Jones, 2017); practice (see Carter, Biggs, and Boehm, 2016;Sango and Forrester-Jones, 2019;Bartelli et al, 2020) and policy (Sango and Forrester-Jones, 2014;Whiting and Gurbai, 2015) indicate that little attention has been paid to this aspect of people's lives; whilst the spiritual rights of children are recognised in the United Nations Convention on the Rights of the Child (UNCRC) they do not feature in the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) (see Whiting and Gurbai, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the few studies that exist in relation to spirituality and people with ID (see Swinton, 2002 ;Liu, Carter, Boehm, Annandale and Taylor, 2014 and Rambow's 2016 unpublished Master's thesis ) have found that a belief in God or a higher power and participation in religious rituals can provide a framework within which individuals can make sense of their life experiences as well as affording them with a sense of security, acceptance and hope, and providing them with a significant source of comfort and a route to social support networks (see Forrester-Jones et al, 2006;Biggs and Carter, 2016;Sango and Forrester-Jones, 2019 and the doctoral thesis by Bacon, 2021). Carter (2021, 2021a, 2021b) further emphasised how a sense of belonging which is rooted in relationships and characteristics of reciprocal relationships such as love and acceptance (Carter, Biggs and Boehm, 2016;Carter and Bohern, 2019) may be found through participation in shared spiritual practices and congregational activities, Hunter and Kivisto (2019) found strong allegiances to religious faith by young people with ID.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Sango and Forrester-Jones (2019, p. 150) define spirituality as "faith in the sacred, a personal relationship with a supreme power". Studies investigating spirituality have explored how it is used to understand stressful situations, and to help with coping (Boehm & Carter, 2019;Sango & Forrester-Jones, 2019). Spirituality has also been associated with resilience in families during times of distress (Walsh, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have investigated the role of spirituality for people with ID themselves have reported that, like those without ID, and like other people with disabilities, people with ID have religious and spiritual affiliations which provide meaning and purpose to their lives, and assist them in coping with stressful life events such as loss and mental illness, amongst others (Boehm & Carter, 2019;Markham, 2006;Mugeere et al, 2019;Ndlovu, 2016;Sango & Forrester-Jones, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Religious communities have been found to act as conduits to social inclusion and community participation (Sango & Forrester-Jones, 2017). They also foster a sense of belonging, emotional wellbeing and spiritual nourishment (Baumeister & Leary, 1995), with spirituality having been shown to play a meaningful part of disabled people's lives, including autistic people (Turner et al, 2004;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%